2013
DOI: 10.4314/ajtcam.v11i1.26
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective and antioxidant effects of the methanol extract of <i>Eremomastax Speciosa</i> in rats

Abstract: Background: Ethno-botanical information shows that Eremomastax speciosa is used in the traditional management of various stomach complaints including gastro-duodenal ulcers. Materials and Methods:In this study, we tested the cytoprotective potential of the whole plant methanol extract (100-200 mg/kg, p.o), against HCl/ethanol, absolute ethanol, cold/restraint stress rats, and pylorus legated rats pre-treated with indomethacin. The effects of the extract on gastric lesion inhibition, the volume of gastric juice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…Overproduction of ROS/RNS activates lipid peroxidation, evidenced by increased MDA levels in gastric mucosa at 24 hours after burn trauma. It has been reported that the increased lipid peroxidation levels in plasma (19,28) and gastric mucosa (29), and the decreased antioxidant defense cause oxidative damage of gastric mucosa, induced by burns (29), NSAID, ethanol, cold/restraint stress treatment (30).…”
Section: Discussionmentioning
confidence: 99%
“…Overproduction of ROS/RNS activates lipid peroxidation, evidenced by increased MDA levels in gastric mucosa at 24 hours after burn trauma. It has been reported that the increased lipid peroxidation levels in plasma (19,28) and gastric mucosa (29), and the decreased antioxidant defense cause oxidative damage of gastric mucosa, induced by burns (29), NSAID, ethanol, cold/restraint stress treatment (30).…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus is a risk factor for erectile dysfunction [ 36 ], and long-term use of histamine H 2 receptor antagonists (e.g., Cimetidine) in gastroduodenal ulcer treatment leads to reduced libido. E. speciosa has been cited for its ethnopharmacological application in diabetes management [ 14 ] and other workers [ 10 , 37 ] have reported the cytoprotective and antisecretory effects of E. speciosa extract in peptic ulcer management. Therefore E. speciosa extract may have possible long-term benefits in sustaining increased levels of libido especially when used to treat conditions that represent risk factors for erectile dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the display of pelvic thrusting during intromission and ejaculation by the extract-treated animals in this study further indicated that the male copulatory organ was in contact with the vaginal orifice which might have activated or strengthened lordosis in the female rats. A postejaculatory interval (PEI) of more than 5400 seconds indicates that the male is sexually exhausted and the intensity of sexual behavior will be reduced in subsequent mating [ 37 ]. In addition, reduction of the postejaculatory interval (PEI) is also an indication of sustained increase in sexual activity [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in a preliminary study, the water extract of E. speciosa significantly inhibited the formation of gastric lesions induced by HCl/ethanol and pylorus ligation [ 16 ]. Subsequent studies demonstrated the cytoprotective and antioxidant activities of the methanolic extract against various experimental ulcer models [ 17 ]. Other works demonstrated that the antisecretory action of the aqueous extract occurs through a mechanism common to both antihistaminic and anticholinergic pathways [ 18 ].…”
Section: Introductionmentioning
confidence: 99%